Estado del arte para la línea de investigación en Responsabilidad Social del Convenio Universidad Santo Tomás e Icontec (2010)
Social Responsibility is an emerging field of organizational management that focuses on understanding and meeting the needs of the different stakeholders that converge in an organization. In the postgraduate studies of the St. Thomas University and Icontec Covenant, the research on “Quality and Social Responsibility” has a focus on the production, development, validation and application of knowledge on this subject, which requires a reference plane that supports investigative intentions. This article summarizes the first phase of a State of the Art in Social Responsibility for the Colombian context, which seeks to provide the datum line of research.